2015
DOI: 10.1021/acs.jmedchem.5b00529
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Selective and Stereoselective Inhibition of Hypoxia Inducible Factor-2

Abstract: Hypoxia inducible factor (HIF) transcription factors reside at the center of signaling pathways used by mammalian cells to sense and respond to low oxygen levels. While essential to maintain oxygen homeostasis, misregulation of HIF protein activity correlates with tumor development and metastasis. To provide artificial routes to target misregulated HIF activity, we identified small molecule antagonists of the HIF-2 transcription factor that bind an internal cavity within the C-terminal PAS domain of the HIF-2α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 42 publications
5
68
0
Order By: Relevance
“…This model subsequently guided the authors to mutate surface amino-acid residues on each subunit (HIF-2α R247E and ARNT E362R), so as to create an artificial salt bridge that could further enhance the binding affinity of two PAS-B domains and facilitate their co-crystallization (Figure 1d) [15]. This artificial PAS-B heterodimer structure not only correlated with the original NMR-based model that two domains can form an interface via their β-sheets in an anti-parallel fashion, but more importantly revealed a large cavity (~300 Å 3 ) with the HIF-2α PAS-B domain [1619]. …”
Section: Overall Structures Of Bhlh-pas Heterodimerssupporting
confidence: 58%
“…This model subsequently guided the authors to mutate surface amino-acid residues on each subunit (HIF-2α R247E and ARNT E362R), so as to create an artificial salt bridge that could further enhance the binding affinity of two PAS-B domains and facilitate their co-crystallization (Figure 1d) [15]. This artificial PAS-B heterodimer structure not only correlated with the original NMR-based model that two domains can form an interface via their β-sheets in an anti-parallel fashion, but more importantly revealed a large cavity (~300 Å 3 ) with the HIF-2α PAS-B domain [1619]. …”
Section: Overall Structures Of Bhlh-pas Heterodimerssupporting
confidence: 58%
“…In addition, conditioned media from esophageal cells that were treated with acidic bile salts were found to increase T cell migration rates in a transwell system. Finally, HIF-2α knockdown by shRNA and HIF-2α inhibition using a selective small molecule antagonist (S,R)-4 (Figure 2) [13] blocked the increases in pro-inflammatory molecule expression and T cell migration induced by acidic bile salts [12]. [Note that (S,R)-4 was named (S,R)-37 Peak 2 in Reference 12] These observations support the hypothesis that reflux esophagitis develops through a cytokine-mediated process in which HIF-2α plays a central role (Figure 1).…”
Section: Hypoxia-inducible Factor-2α: a Key Mediator Of The Cytokine mentioning
confidence: 99%
“…Subsequent to this original study, Bruick, Gardner, MacMillan, and Tambar identified a more potent class of inhibitors of HIF-2α–HIF-β heterodimerization, which are based on a tetrazolo-tetrahydropyrimidine ring system ( 3 , Figure 2b) [13]. This general pharmacophore is preferred over compound 2 for several reasons.…”
Section: Isoform-selective Hif-2α Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2003 an increasing structural knowledge on homologous proteins belonging to the bHLH-PAS family has become available and has greatly contributed to advancements in molecular understanding of the AhR structure and interactions [2634]. In addition to well-conserved N-terminal domain structures, the bHLH-PAS proteins show similarities in the mechanisms of action [35,36].…”
Section: Molecular Insightsmentioning
confidence: 99%